The phenomenological paradigm of Gestalt psychotherapy - JAWOR, MAREK (Filozofia Chrześcijańska, 2021)
This article examines the influence of the assumptions of the phenomenological method on the shape of Gestalt psychotherapy. Therefore, a comparative analysis of the main ideas of Edmund Husserl’s philosophy and the basic assumptions of Gestalt psychotherapy was performer. The strenght and importance of the underlying connections are indicated by both research methods used in Gestalt therapy: the directness of experiencem „suspedding” one’s own beliefs, horizontal description, and categories related to awareness: contact intentionality and „here and now” experience.